Caracterización sociodemográfica de la población desplazada de la vereda Granizal del municipio de Bello, Antioquia (2017)
ABSTRACT: The demographic study of Vereda Granizal the Municipality of Bello-Antioquia, was an exercise conducted between the Office of the UN High Commissioner - UNHCR and research group KABAI organizations, Faculty of Business Administration of the University Autónoma Latinomericana, two purposes: to establish the living conditions of the people at the Vereda who have suffered forced displacement and indicate critical variables regarding the effective enjoyment of rights defined by the Colombian Constitutional Court.